Designing Defence Aerospace Supply Chain Services to Enhance Customer Value - Davey, Robert (2015)
Manufacturing organisations traditionally created value for customers by designing, producing, and selling finished goods. Through the emergence of servitization, product-service-systems evolved; value creation from servicing activities that support product lifecycles gained prominence. Business operating models were realigned to deliver value from cross-functional business activities, geared towards gaining an advantage over competitors. Today, business activities need to be viewed as complex living systems, where exchanges between participants takes place to create value for increasingly demanding customers. This dissertation applies Value Network Analyses (VNA) to Rolls-Royce Plc Defence Aftermarket supply chain services, to identify and analyse tangible and intangible value exchanges, currently supporting the UK Ministry of Defence (MoD) RAF fast jet and helicopter engine programmes. Focus groups were used as a tool for qualitative data collection, to identify themes and gaps between the As Is value networks, and the expected To Be value networks required to support a new RAF in-service engine programme, named TP400, which provides the Case Study focus for this research. The UK MoD operating strategy and expectations of procurement relationships with industry are changing; this study identifies themes important to the customer, and recommends improvement measures to be taken in order to design supply chain services that enhance value for the customer.